An investigation of surface texture parameters during turning of a reinforced polymer composite using design of experiments and analysis. (15th December 2009) - Kechagias, John; Petropoulos, George; Iakovakis, Vassilis; Maropoulos, Stergios
The influence of cutting speed and feed rate during turning on the arithmetic mean roughness (Ra), the maximum peak to valley (Rt), and the fractal dimension (D) of a glass fibre polymer composite (Ertalon 66 GF-30) was experimentally investigated. Test specimens in the form of bars and a P20 cemented carbide cutting tool were used with the cutting depth kept constant during the experiment. Robust design using an orthogonal matrix experiment was conducted and the experimental results were analysed using an ANOM and an ANOVA analysis approach. Based on the statistical analysis of the experimental results it was found that the arithmetic mean roughness, the maximum peak to valley and the fractal dimension depend mainly on the feed rate parameter. Also, based on the interaction charts and evaluation experiments it was found that regression modelling applies only for the arithmetic mean roughness.